Diversity of soil fauna in soils with different management systems in the north of Rio Grande do Sul (Research, Society and Development, 2022)
The soil fauna generates important environmental services, which can be negatively affected by different soil management. Thus, the present work aims to evaluate the diversity of the built fauna in soils with different management systems in Southern Brazil. The work was carried out in Inhacorá, RS, in Ultisol, between December 2016 and February 2017, consisting of four areas under no-tillage system: ILP (Crop-Livestock Integration), annual pasture (PA), fruits ( FT) and grain harvesting (LG). A randomized complete block design with eight replications was used. One fauna was sampled by the Provid method and eight traps per treatment were used, randomly distributed. In the first time studied the ILP area was significantly higher in relation to the total number of organisms, while in the second collection there was no significant difference in relation to the total number of organisms between the studied areas. Regarding richness, especially in the first collection season, the LG and TF areas provided the greatest diversity, with 14 orders, in the PA area 13 orders were found and in the ILP area 12 orders, while in the second collection all the areas showed a diversity decrease. The Collembola order presented the largest number of organisms in both collections, highlighting the ILP area in the first collection. Thus, the edaphic fauna was influenced by the different managements and the different collection times.